(untitled) (Journal of Applied Oral Science, 2023)
Background: Osteogenesis imperfecta (OI) is a rare genetic disorder primarily caused by mutations in the genes involved in the production of type 1 collagen. OI is also known as brittle bone disease. Objective: This study aims to describe the prevalence of dental anomalies (except dentinogenesis imperfecta) in individuals with OI, and compare the prevalence of dental anomalies between individuals with and without OI and between individuals with different types of OI. Search methods: Searches in PubMed, Web of Science, Scopus, Ovid, and gray literature were performed in October 2022. Selection criteria: Observational studies (with or without a comparison group) that evaluated the prevalence of dental anomalies in individuals with OI. Data collection and analysis: Data items were extracted by two authors. Quality assessment employing the Joanna Briggs Institute checklists and meta-analyses was conducted. Results were provided in prevalence values and odds ratio (OR) / 95% confidence interval (CI). Strength of evidence was determined. Results: Eighteen studies were included. Most prevalent dental anomalies in individuals with OI included pulp obliteration (46.4%), dental impaction (33.5%), dental impaction of second molars (27%), and tooth agenesis (23.9%). Individuals with OI type III/IV had 20.16-fold greater chance of exhibiting tooth discoloration in comparison with individuals with OI type I (CI: 1.10–370.98). In comparison with the group without OI, the individuals with OI had 6.90-fold greater chance of exhibiting dental impaction (CI: 1.54–31.00). High methodological quality was found in 47% of the studies. Strength of evidence was low or very low. Conclusions: Pulp obliteration, dental impaction, and tooth agenesis were the most prevalent dental anomalies in the OI group. Individuals with OI were more likely to have dental impaction than individuals without OI. Individuals with OI type III/IV (severe-moderate) are more likely to have tooth discoloration than individuals with OI type I (mild).